Evidence of cognitive chunking in freehand sketching during design ideation. (March 2020) - Mao, Xiaoyang; Galil, Omar; Parrish, Quintcey; Sen, Chiradeep
Abstract : This paper reports a human-subject protocol study examining the cognitive process of freehand sketching during design ideation and presents empirical evidence for the presence of chunking during sketching. Volunteer designers sketched solution concepts to unseen design problems using a homegrown software program on a tablet computer to draw their sketches, which performed a time study and identified pen stroke clusters. These clusters were found to be strongly correlated with the sketched objects that the designers voluntarily named during labelling, irrespective of the object's containment level in the sketched solution. The frequent occurrence of single-private clusters, where all pen strokes in a cluster are used to draw a single named object, provides evidence for cognitive chunking during ideation sketching. Highlights: When designers sketch novel ideas, their thought forms little packets called chunks. The chunks cause a cluster pattern in the designers' use of the pen when sketching. Each meaningful object within the sketch gets its own chunk and its own cluster. A new experimental software program automates the protocol analysis used here. The experimental software allows viewing the chunks in real time.